Genome sequencing and analysis of two early-flowering cherry (Cerasus × kanzakura) varieties, 'Kawazu-zakura' and 'Atami-zakura'. (18th November 2021) - Shirasawa, Kenta; Itai, Akihiro; Isobe, Sachiko
Abstract: To gain genetic insights into the early-flowering phenotype of ornamental cherry, also known as sakura, we determined the genome sequences of two early-flowering cherry ( Cerasus × kanzakura ) varieties, 'Kawazu-zakura' and 'Atami-zakura'. Because the two varieties are interspecific hybrids, likely derived from crosses between Cerasus campanulata (early-flowering species) and Cerasus speciosa, we employed the haplotype-resolved sequence assembly strategy. Genome sequence reads obtained from each variety by single-molecule real-time sequencing (SMRT) were split into two subsets, based on the genome sequence information of the two probable ancestors, and assembled to obtain haplotype-phased genome sequences. The resultant genome assembly of 'Kawazu-zakura' spanned 519.8 Mb with 1, 544 contigs and an N50 value of 1, 220.5 kb, while that of 'Atami-zakura' totalled 509.6 Mb with 2, 180 contigs and an N50 value of 709.1 kb. A total of 72, 702 and 69, 528 potential protein-coding genes were predicted in the genome assemblies of 'Kawazu-zakura' and 'Atami-zakura', respectively. Gene clustering analysis identified 2, 634 clusters uniquely presented in the C. campanulata haplotype sequences, which might contribute to its early-flowering phenotype. Genome sequences determined in this study provide fundamental information for elucidating the molecular and genetic mechanisms underlying the early-flowering phenotype of ornamental cherry tree varieties and their relatives.